Improvising Organizational Strategies by Engaging Stakeholders and Fostering Behavioural Change Through AI Techniques - Leinonen, Mirva Sari Liisa (Digital Repository of Theses, 2026)
This DBA thesis examines how professionals and managers in the financial sector experience change related to artificial intelligence (AI) and how these experiences affect the requirements for just management and just decision-making. The study consists of 33 semi-structured interviews conducted with 31 financial sector professionals and managers, as well as a manager from an engineering services field and a psychopractitioner. The data was analysed using thematic qualitative analysis, which was supported by inductive reasoning. The findings reveal a significant experiential gap as managers describe themselves as supportive and people-oriented, while financial services professionals perceive leadership as distant and number-driven during the digital transformation. Tacit knowledge is considered essential, but the importance of it is still widely unrecognized, and systems for sharing expertise are limited. The integration of AI also presents challenges learning cultures and highlights the importance of psychological safety, reflective thinking, and shared meaningfulness. From a managerial and practical perspective, the findings highlight the need to strengthen human-centered management, create systematic practices for knowledge sharing, and support lifelong learning during AI transition. The DBA thesis proposes the concepts of Just Management and Just Decision‑Making to examine how justice and participation can be integrated into management structures, leadership practices and AI‑assisted decision processes. In addition, the HAIC-SECI model is presented as a framework for incorporating tacit This DBA thesis examines how professionals and managers in the financial sector experience change related to artificial intelligence (AI) and how these experiences affect the requirements for just management and just decision-making. The study consists of 33 semi-structured interviews conducted with 31 financial sector professionals and managers, as well as a manager from an engineering services field and a psychopractitioner. The data was analysed using thematic qualitative analysis, which was supported by inductive reasoning. The findings reveal a significant experiential gap as managers describe themselves as supportive and people-oriented, while financial services professionals perceive leadership as distant and number-driven during the digital transformation. Tacit knowledge is considered essential, but the importance of it is still widely unrecognized, and systems for sharing expertise are limited. The integration of AI also presents challenges learning cultures and highlights the importance of psychological safety, reflective thinking, and shared meaningfulness. From a managerial and practical perspective, the findings highlight the need to strengthen human-centered management, create systematic practices for knowledge sharing, and support lifelong learning during AI transition. The DBA thesis proposes the concepts of Just Management and Just Decision‑Making to examine how justice and participation can be integrated into management structures, leadership practices and AI‑assisted decision processes. In addition, the HAIC-SECI model is presented as a framework for incorporating tacit